P66 SVR with telaprevir, peginterferon alfa-2A and ribavirin in HCV patients with well-characterised prior null response, partial response, viral breakthrough or relapse after peginterferon+ ribavirin. (16th November 2010) - Dusheiko, G; Berg, T; Pawlotsky, J M; Ferenci, P; Zeuzem, S; Muir, A J; Poordad, F; Shiffman, M L; Heathcote, J; Reesink, H; Adda, N; McHutchison, J G
Abstract : Introduction: Study107 is an open-label rollover study of telaprevir (T) with peginterferon+ ribavirin (PR) in genotype-1 HCV patients who did not achieve SVR following PR treatment in telaprevir Phase 2 studies. Method: Null responders (<1-log10 HCV RNA decrease at week-4 or <2-log10 at week-12), partial responders (=2-log10 decrease at week 12, detectable at week 24), patients with viral breakthrough and relapsers from PROVE1/2/3 PR arms were eligible for treatment. Initially all patients received T 750 mg q8h plus PR at standard doses for 12 weeks, followed by 12 weeks of PR (T12/PR24). Protocol was amended to allow partial responders, viral breakthroughs and relapsers with undetectable HCV RNA at weeks 4 and 12 (eRVR) to receive T12/PR24. Partial responders, viral breakthroughs and relapsers with detectable HCV RNA at week 4 and/or week 12 and null responders received an additional 24 weeks of PR (T12/PR48). Results: Of 117 patients included in an ITT analysis, 97 (83%) had baseline HCV RNA=800 000 IU/ml, (69) 59% had genotype subtype 1a, 44 (38%) had cirrhosis or bridging fibrosis, and 9 (8%) were black. Viral breakthrough and relapse rates occurred in 25%, 23% of prior null responders; 10%, 22% of prior partial responders; 13%, 0% of prior viral breakthroughs; and 0%, 4% of prior relapsers. Conclusion: Patients with prior relapse, breakthrough and partial response exhibited high SVR rates after 24 weeks of telaprevir-based regimen. High SVR rates were also observed in patients with previous null response after 48 weeks of therapy.